Identification of seasonal influenza virus in the Northern Vietnam, 2013-2015 - Thi Thanh Loan, Tran; Thi Viet Ha, Bui; Thi Quynh Mai, Le; Thi Thanh, Le; Thi Hong Trang, Ung; Thi Hien, Pham; Thi Thu Huong, Tran; Le Khanh Hang, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4598, 2017)
Monitoring of influenza virus subtypes has provided the useful information for the Global Influenza Surveillance and Response System (GISRS) in influenza vaccines development to improve vaccine efficacy. A number of influenza A/H1N1pdm09, A/H3N2 and B viruses by RT-PCR from human clinical specimens collected from 2013 to 2015 in Northern Vietnam were isolated on MDCK-SIAT1 cells and identified by hemagglutination inhibition assay (HAI). The data reported here confirmed that MDCK-SIAT1 cells could be used efficiently in order to isolate influenza A/H1N1pdm09, A/H3N2 and B viruses with an average isolation rate of 59.25%. All A/H3N2 viruses were better recovered from MDCK-SIAT1 cells with low viral titer than influenza A/H1N1pdm09 and influenza B viruses. Almost all Vietnamese isolates were inhibited by ferret antisera raised against reference viruses with similar HAI titer recommened by WHO annually. A small proportion of viruses showed changed reactivity by HAI, reduced of virus neutralization in all influenza subtypes, in which the influenza A/H3N2 virus had the highest number: 2013 (4.9%), 2014 (1.9%) and 2015 (8.9%).